The Chicago Black renaissance and women's activism - Knupfer, Anne Meis (University of Illinois Press, 2006)
The untold story of the prodigious activism of African American women on Chicago's south side Following on the heels of the Harlem Renaissance, the Chicago Renaissance was a resonant flourishing of African American arts, literature, theater, music, and intellectualism, from 1930 to 1955. Anne Meis Knupfer’s The Chicago Black Renaissance and Women’s Activism demonstrates the complexity of black women’s many vital contributions to this unique cultural flowering. The book examines various groups of black female activists, including writers and actresses, social workers, artists, school teachers, and women’s club members to document the impact of social class, gender, nativity, educational attainment, and professional affiliations on their activism. Together, these women worked to sponsor black history and literature, to protest overcrowded schools, and to act as a force for improved South Side housing and employment opportunities. Knupfer also reveals the crucial role these women played in founding and sustaining black cultural institutions, such as the first African American art museum in the country; the first African American library in Chicago; and various African American literary journals and newspapers. As a point of contrast, Knupfer also examines the overlooked activism of working-class and poor women in the Ida B. Wells and Altgeld Gardens housing projects.